KEBENARAN HEGEMONIK AGAMA - Hasbiyallah, Hasbiyallah; Solahuddin, Solahuddin; Munawar, Slamet; Utomo, Budi (Asosiasi Dosen PTKIS Indonesia, 2025)
Anarchic violence against jamaah Ahmadiyah and “Aliansi Kebangsaan untuk Kebebasan Beragama dan Berkeyakinan (AKKBB)” by Front Pembela Islam (FPI) constitutes a form of truth claim among religious groups in religious society. The religious interpretation which formerly opened now reduced to become the closed interpretation. The formerly is the substantive interpretation now become the hegemonic interpretation. This is one of the greatest theological challenge facing by religious community. This article will show the patterns of attitude and idea among religious comminity members which stimulate hegemonic truth claim in order to find out the friendly, egalitarian, and tolerant forms of religions, so the hegemonic truth claim of the religion should be avoided.